Integration of Material Flow Cost Accounting and Resource Efficiency into Green Accounting: A Strategy for Company Sustainability - Said, Darwis; Sukoharsono, Eko Ganis; Darmawati, Darmawati; Juanda, Muhammad Reza Pahlevi; Amalia, Alia Rezki; Madein, Afdal (Journal of Environmental Accounting and Management, 2026)
This research aims to explore the impact of green accounting on corpo- rate sustainability by incorporating the MFCA approach and assessing resource efficiency. The samples for this study comprise 23 manufacturing companies listed on the Indonesian Stock Exchange (IDX) from 2020 to 2022. Data collection involved reviewing the selected companies’ annual and sustainability reports. The data analysis was conducted using path analysis with the assistance of SmartPLS 4 software. The hypothesis testing results indicate that green accounting and MFCA positively affects corporate sustainability. Green accounting positively affects MFCA but negatively affects resource efficiency. MFCA mediates the relationship between green accounting and corporate sustainability. However, resource efficiency has not effectively mediated the relationship between green accounting and corporate sustainability. This pioneering research is the first to combine green accounting with MFCA within the context of manufacturing companies in Indonesia. It provides a fresh perspective on MFCA’s role as a mediator between green accounting and corporate sustainability. This research underscores the importance of integrating green accounting and MFCA in the management strategies of manufacturing companies to improve long-term sustainability while seeking solutions to overcome the negative influence of green accounting on resource efficiency. This research emphasizes the importance of adopting green accounting and MFCA practices to reduce manufacturing activities’ negative environmental impacts, positively contribute to society through reduced waste and emissions, and improve resource use efficiency.